Dietary κ-carrageenan facilitates gut microbiota-mediated intestinal inflammation. (1st February 2022) - Wu, Wei; Zhou, Jiawei; Xuan, Rongrong; Chen, Juanjuan; Han, Hui; Liu, Jingwangwei; Niu, Tingting; Chen, Haimin; Wang, Feng
Abstract: The inflammatory effects of carrageenan (CGN), a ubiquitous food additive, remains controversial. Gut microbiota and intestinal homeostasis may be a breakthrough in resolving this controversy. Here we show that, κ-CGN did not cause significant inflammatory symptoms, but it did cause reduced bacteria-derived short-chain fatty acids (SCFAs) and decreased thickness of the mucus layer by altering microbiota composition. Administration of the pathogenic bacterium Citrobacter rodentium, further aggravated the inflammation and mucosal damage in the presence of κ-CGN. Mucus layer degradation and altered SCFA levels could be reproduced by fecal transplantation from κ-CGN-fed mice, but not from germ-free κ-CGN-fed mice. These symptoms could be partially repaired by administering probiotics. Our results suggest that κ-CGN may not be directly inflammatory, but it creates an environment that favors inflammation by perturbation of gut microbiota composition and then facilitates expansion of pathogens, and this effect may be partially reversed by the introduction of probiotics. Graphical abstract: Unlabelled Image